Sepsis and septic shock associated to female genital tract infection - Cerna Barco, Jorge (2015)
The presence of sepsis or septic shock in a woman in fertile age results one of the greatest worries of modern medicine, not only by the impact in a person in productive age but because infections that complicate these patients usually result from an inadequate application of biosecurity measures and infection prevention in the health system. In this review we present conditions associated to a higher prevalence of infections in the woman in fertile age, septic shock causes, types of acute pelvic inflammatory disease, causative agents of higher genital tract infections, sepsis pathogenesis, clinical presentation, etiological diagnosis, initial resuscitation and antibiotic therapy and criteria of hospitalization. We wish this presentation be a contribution on sepsis and shock management in an intensive care unit.